“The country of his past”: Homecoming in “A Modern Lover” and “The Shades of Spring” - Keith Cushman (Études Lawrenciennes)
In the two early stories, “A Modern Lover” and “The Shades of Spring,” Lawrence imagines an autobiographical figure returning to his home country to renew connection with the young woman he had loved (a version of Jessie Chambers). The two “homecoming” stories are intriguing add-ons to the Miriam Leivers material in Sons and Lovers. In “A Modern Lover” the returning protagonist is callow and self-centered, but his old sweetheart is still attracted to him. In “The Shades of Spring,” the returning protagonist discovers that his newly self-confident, “very womanly” former sweetheart is having an affair with a young gamekeeper. The differences between the stories and their main characters illuminate Lawrence’s personal and artistic growth between the composition of “A Modern Lover” in 1909 and the final revision of “The Shades of Spring for the Prussian Officer collection in the summer of 1914.